Mapping Tourist Attractions and Analyzing Travel Patterns in Jembrana Regency, Bali, Indonesia - Agus Muriawan Putra; Nyoman Ariana; Agung Suryawan Wiranatha; Putu Perdana Kusuma Wiguna; I Gusti Bagus Arya Yudiastina (Journal of Applied Sciences in Travel and Hospitality, 2026)
Bali Province is one of Indonesia’s leading tourism regions; however, empirical studies examining the spatial distribution of tourist attractions and tourist travel patterns at the regency scale remain limited, particularly in peripheral areas such as Jembrana Regency. This study addresses this gap by mapping the spatial distribution of tourist attractions and analyzing tourist travel patterns in Jembrana Regency. A spatial/GIS-based approach was employed by integrating secondary data from official tourism documents with field surveys, followed by geographic plotting and clustering based on administrative boundaries, accessibility, and spatial proximity. Tourist attractions were classified into four clusters: East (Pekutatan District), Central-East (Mendoyo District), Central-West (Jembrana District), and West (Negara and Melaya Districts). Tourist travel patterns were analyzed using observations, interviews, and Focus Group Discussions (FGDs), focusing on movement flows, travel routes, and visitation sequences. Destinations with high visitor numbers, strategic locations, and adequate amenities were identified as tourism hubs, including Medewi Beach, Pelataran Rambut Siwi, Perancak Village, Gilimanuk Bay, Blimbingsari Tourism Village, and Candikusuma Beach. The Denpasar–Gilimanuk road emerges as the primary corridor shaping accessibility and inter-cluster tourist mobility. The findings reveal that tourist movements follow structured spatial patterns influenced by accessibility, destination hierarchy, and geographic configuration. These results highlight the importance of integrated spatial planning, infrastructure enhancement, targeted destination promotion, and community capacity development to support balanced and sustainable tourism development in Jembrana Regency.